Effects of Kinesio taping on scapular kinematics of overhead athletes following muscle fatigue - Garcia Zanca, G.; Grüninger, B.; Mattiello, S. M. (Journal of Electromyography and Kinesiology, 2016)
Scapular kinematics alterations have been found following muscle fatigue. Considering the importance of the lower trapezius in coordinated scapular movement, this study aimed to investigate the effects of elastic taping (Kinesio taping, KT) for muscle facilitation on scapular kinematics of healthy overhead athletes following muscle fatigue. Twenty-eight athletes were evaluated in a crossover, single-blind, randomized design, in three sessions: control (no taping), KT (KT with tension) and sham (KT without tension). Scapular tridimensional kinematics and EMG of clavicular and acromial portions of upper trapezius, lower trapezius and serratus anterior were evaluated during arm elevation and lowering, before and after a fatigue protocol involving repetitive throwing. Median power frequency decline of serratus anterior was significantly lower in KT session compared to sham, possibly indicating lower muscle fatigue. However, the effects of muscle fatigue on scapular kinematics were not altered by taping conditions. Although significant changes were found in scapular kinematics following muscle fatigue, they were small and not considered relevant. It was concluded that healthy overhead athletes seem to present an adaptive mechanism that avoids the disruption of scapular movement pattern following muscle fatigue. Therefore, these athletes do not benefit from the use of KT to assist scapular movement under the conditions tested.